Academic emotions of eighth grade students in algebra classrooms using an artificial intelligence learning environment - Omar, Amal; Daher, Wajeeh; Bayaa, Nimer (Frontiers in Education, 2025)
IntroductionWith the increasing use of artificial intelligence (AI) in education, there is a need to investigate the emotional impact of smart learning environments. This study explores the impact of using the AI-powered CK-12 Flexi (v2.0) application on the academic emotions of eighth-grade students while learning algebra.MethodsA mixed-methods approach was applied to a sample of 92 male and female students from two schools in Nablus, selected via convenience sampling and distributed into two groups: an experimental group (learned using the Flexi application) and a control group (learned using the traditional method). Quantitative data were collected through pre- and post-questionnaires addressing academic emotions; qualitative data were collected through semi-structured interviews with a selected sample of students from the experimental group.ResultsPretest-adjusted Quade nonparametric ANCOVA with Holm–Bonferroni control across six outcomes showed significant group differences favoring the experimental group for enjoyment (higher) and for anxiety and boredom (lower), padj ≤ 0.036; effects were small-to-moderate (partial, η2 = 0.074–0.116). In contrast, shame, pride, and anger did not differ significantly after correction. Qualitative results reflected a comprehensive picture of students’ experience, revealing diverse positive emotions such as enthusiasm, comfort, and enjoyment, as well as negative emotions such as anxiety resulting from technical and interactive challenges, in addition to students’ dissatisfaction given their heavy reliance on the app.DiscussionThe study was primarily grounded in Control-Value Theory (CVT)—viewing academic emotions as functions of perceived control and value—while Self-Determination Theory (SDT) served as a complementary interpretive lens to explain how the intervention might support autonomy, competence, and relatedness.